Diocesan Year Book 1956 (UK The Authority of The Archbishop Bishop of Portsmouth, 1956)
Eighth Annual Publication . Church of England in Canada. Diocese of Nova Scotia
V . Diocese of Portsmouth . BX1750.A1
Church of England in Canada. Diocese of Nova Scotia. Year book
Keywords: History of Christianity: Miscellaneous (3JGQjN GdeSjMjI(B: (3eJaQbGJs